75.00+25h=40h

Simple and best practice solution for 75.00+25h=40h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 75.00+25h=40h equation:


Simplifying
75.00 + 25h = 40h

Solving
75.00 + 25h = 40h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-40h' to each side of the equation.
75.00 + 25h + -40h = 40h + -40h

Combine like terms: 25h + -40h = -15h
75.00 + -15h = 40h + -40h

Combine like terms: 40h + -40h = 0
75.00 + -15h = 0

Add '-75.00' to each side of the equation.
75.00 + -75.00 + -15h = 0 + -75.00

Combine like terms: 75.00 + -75.00 = 0.00
0.00 + -15h = 0 + -75.00
-15h = 0 + -75.00

Combine like terms: 0 + -75.00 = -75
-15h = -75

Divide each side by '-15'.
h = 5

Simplifying
h = 5

See similar equations:

| 4+2[4-(3+y)]=-2(y-1)-4+y | | x^3-4x^2+8x-32=0 | | abs(3x-4)=6 | | 4Q+7=-12 | | (3m-6/2)5 | | 220=2x-12c | | (5x-3)+(6x-17)=90 | | 1/2x+1/6x=4 | | 2-5(4-3x)=2(4-x)-8x | | x^3-3x^2+3p-0.95=0 | | 6/7(14z-7)=0 | | (5x-3)+(6x-17)=180 | | 48+6y=0 | | 12z+6-2z=-5z+3(5z+3) | | -12-(-9)/(-3) | | x+4/11=x-2/9 | | 13x^2-8y-9=0 | | -2(15y-2)+30y=4 | | 6z+2(z+3)=2(4z+3) | | 6x-7y=-49 | | v/3+10=15 | | 5b-6=5(b-14) | | 5w-8=52 | | c^2=-35-12c | | -1/2x+3/11=15/22 | | .07(3y+5)=.2(y-5) | | 2*11.25=90 | | .5(3x-4)-.7=.4(5+4x) | | 8b+3(2b+2)=11 | | 8v-12+5v=5v+10-3v | | 7(3x-1)=5+4(x-3) | | -4k-8+11=-3k-12 |

Equations solver categories